Sustainability Risk Analysis of the Halal Feed Supply Chain for Ruminant Commodities Through the Integration of the SCOR-FMEA Method - Wahyuni, Hana Catur; Permata Sari Hartanti, Lusia; Marodiyah, Inggit; Wahyu Setya Kurniawan, Muhammad; binti Pauzi, Norhidayah (Spektrum Industri, 2026)
Ruminant commodities play a strategic role in maintaining the stability of meat and milk supply for society. In this context, feed serves not only as a key determinant of livestock productivity but also as a critical foundation for environmental sustainability and compliance with halal standards throughout the supply chain. This study aims to map and priorities risks in the ruminant feed supply chain through the integration of the SCOR and FMEA methods. The novelty of this research lies in the integration of sustainability risks with halal-related risks within the supply chain framework. The study was conducted in Gendro Village, Pasuruan Regency. Data were collected through expert assessments of severity, occurrence, and detection levels, taking into account economic, environmental, and socio-halal aspects. The SCOR framework was applied to systematically map sustainability and halal risks along the supply chain, while FMEA was used to determine risk priorities based on the Risk Priority Number (RPN). The findings indicate that the highest RPN values occur in the planning process, particularly in traceability system planning (R5), and in the production process related to product tracking and record-keeping activities (R20). In addition, the study reveals several halal compliances risks that are difficult to detect, including document verification, segregation practices, and line clearance procedures. In practical terms, the identified risk priorities and proposed improvements can be directly implemented by farmers, enabling improvements in feed quality, reductions in losses, preservation of halal integrity, and enhancement of supply chain resilience through realistic and low-cost interventions. Overall, this study contributes a risk prioritization model that integrates economic, environmental, and halal dimensions and links mitigation actions to SCOR processes, making it applicable to ruminant feed supply chains as well as other commodity-based supply chains.